The exports of dehusked coconuts from southwestern Ghana: Implications for coconut farmers’ role in a rural virgin coconut oil value chain - Emmanuel Honlah; Alexander Yao Segbefia; David Forkuo; Kabila Abass (Social Sciences and Humanities Open, 2024)
The export of coconuts creates competition between local value chain activities and the export market. This article examined the impact of dehusked coconut exports on the role of coconut farmers in the local virgin coconut oil (VCO) value chain in the Jomoro Municipality, Ghana. The study answered the following question: What were the quantities of coconut farmers supplied to local VCO processors before and during the export periods? Simple random sampling was used to select 311 coconut farmers for the study. Both structured and unstructured interviews were conducted using an interview schedule and a semi-structured interview guide, respectively. Quantitative data were analysed using IBM SPSS (version 25), while direct quotes were used to support the quantitative data. The results show that the presence of coconut exporters and the rising price of coconuts were major opportunities for coconut farmers. Exporters bought 100 dry coconuts at GHȻ100 while the local VCO processors bought the same quantity at GHȻ60. The international market prices for dry (mature) coconuts ranged from €14 to €15 (GH₵98 to GH₵105) per bag of 50 units. The majority of the coconut farmers, therefore, supplied 70–100% of their coconuts to exporters and 10–30% to local VCO processors. Thus, the exports of coconuts, mainly to Nigeria, Europe and the United States of America, have impacted farmers’ roles in the local VCO value chain. The government should partner with local companies to build more processing plants that will offer attractive prices to farmers in order to keep coconuts in the Jomoro Municipality for processing.